(untitled) (Malaysian Journal of Civil Engineering, 2023)
River basin systems involve complex, diverse and dynamic nature. The Malaysia River Basin Sustainability Index (MyRIBASIN) monitors the sustainability status in river basin ecosystems by addressing multi-element involved in river basin systems. The study highlights a link between the multi-criteria in MyRIBASIN as a sound basis for measures design. The multi-criteria judgment aims to define the river basin performance from criteria indicators which Johor River Basin is a case study. The analytic hierarchy process (AHP) weighs four criteria for elements in the river basin: Environment, Social Awareness and Health, Governance and Economic. The group decision-making process is used to assess priorities based on the inputs from Malaysia’s authorities and academicians. Results show that the weighting values for Environment criteria have the highest value, followed by Social and Health, Governance and Economic. The findings show the perception of respondents on the importance of basin conservation and community awareness.